Scots Pine Needles as Bioindicators in Determining the Aerial Distribution Pattern of Sulphur Emissions around Industrial Plants - Risto Pöykiö; Jari Hietala; Hannu Nurmesniemi (Zenodo, 2010)
In this study, the Scots pine (Pinus sylvestris L.) C needles (i.e. the current-year-needles) were used as bioindicators in determining the aerial distribution pattern of sulphur emissions around industrial point sources at Kemi, Northern Finland. The average sulphur concentration in the C needles was 897 mg/kg (d.w.), with a standard deviation of 118 mg/kg (d.w.) and range 740 – 1350 mg/kg (d.w.). According to results in this study, Scots pine needles (Pinus sylvestris L.) appear to be an ideal bioindicators for identifying atmospheric sulphur pollution derived from industrial plants and can complement the information provided by plant mapping studies around industrial plants.